2022
DOI: 10.3390/md21010012
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Dust-Induced Skin Inflammation: Low-Molecular-Weight Fucoidan Protects Keratinocytes and Underlying Fibroblasts in an Integrated Culture Model

Abstract: Prolonged exposure to fine dust (FD) increases the risk of skin inflammation. Stimulated epidermal cells release growth factors into their extracellular environment, which can induce inflammation in dermal cells. Algae are considered rich sources of bioactive materials. The present study emphasized the effect of low-molecular-weight fucoidan isolated from Sargassum confusum (LMF) against FD-induced inflammation in HaCaT keratinocytes and underneath fibroblasts (HDFs) in an integrated culture model. HDFs were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…As erucic acid is considered a toxicant, this compound could be a better cosmetic biomaterial with greater safety for the skin than a functional food additive. According to previous studies [30,31], fine dust causes an increase in ROS in dermal cells, and here we show that erucic acid induced an increase in anti-ROS proteins, including AKT, P52, P50, and BCL2, in fibroblasts (Figure 2).…”
Section: Discussionsupporting
confidence: 87%
“…As erucic acid is considered a toxicant, this compound could be a better cosmetic biomaterial with greater safety for the skin than a functional food additive. According to previous studies [30,31], fine dust causes an increase in ROS in dermal cells, and here we show that erucic acid induced an increase in anti-ROS proteins, including AKT, P52, P50, and BCL2, in fibroblasts (Figure 2).…”
Section: Discussionsupporting
confidence: 87%
“…The protective effect of FSSQ against intracellular ROS production in LPS-stimulated RAW 264.7 macrophages was investigated by using DCF-DA assay [ 15 ]. Following a 24 h incubation period, cells were treated with FSSQ sample doses and incubated for 1 h. Then cells were stimulated with LPS.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, the LMF from S. horneri indicated protective effects via regulating inflammatory reactions and disrupted skin barrier functions in fine-dust-stimulated keratinocytes [ 13 ]. One of our previous studies found that LMF refined by S. confusum on FD-stimulated HaCaT keratinocytes recovered the cells from inflammatory reactions and protected underneath dermal fibroblasts from inflammation and extracellular matrix degradation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidan is a type of natural active polysaccharide mainly extracted from marine brown algae (Pomin, 2015) containing sufficient L-fucose and sulfate eater groups (Li et al, 2008). Fucoidan has been found to be effective at growth promotion (Dawood et al, 2018;Fazio et al, 2019) and gastrointestinal function regulation (Cui et al, 2020;Liu et al, 2020), and to have anti-inflammatory (Kirindage et al, 2022;Wang et al, 2022), anti-oxidation (Sony et al, 2019;Abdel-Daim et al, 2020;Mahgoub et al, 2020), anti-tumor (Han et al, 2015a;Han et al, 2015b;Jin et al, 2022), anti-bacterial (Yu et al, 2015;Zhu et al, 2021), and immunomodulatory (Wang et al, 2019;Ikeda-Ohtsubo et al, 2020) properties. Recently, fucoidan has attracted the attention of aquatic animal researchers.…”
Section: Introductionmentioning
confidence: 99%